PERAN PEMBIAYAAN BAGI HASIL MUDHARABAH DALAM PENGEMBANGAN USAHA NASABAH (Studi pada KANINDO Syariah Jatim) - Munir, Misbahul; Wardani, Mei Dwi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
Islamic financial services unit is designed for the creation of togetherness in bearing the risks and share the results of operations between the owner of the funds that keep their money in banks, with banks and fund managers as well as communities in need of funds to the status of the borrower or fund manager. In this study using qualitative analysis methods, qualitative analysis is a data analysis technique used in describing how the objects of research as well as outlines in the form of sentences or statements based on data collected with the aim to obtain a conclusion from the formulation of the problem. The results of this research show that mudharabah role for business customers looking from business activities managed by the customer. From an initial shortage of capital to the business generate more profits. In addition, mudharabah also have a role to the Indonesian economy. Among them are mudharabah not solely motivated by economic but also social motive that is earmarked for small communities. With mudharabah motives will alienate the public from loan sharks, but it required a very easy terms, and also mudharabah will save the Muslims from the practice of usury which is clearly unlawful. Keywords: pembiayaan, mudlarabah, bagi hasil, shahib al-mal, mudlarib